Aspects of glenoid component wear and disassembly in the Nottingham Total Shoulder Arthroplasty - Gyorgy, Kocsis (2019)
Introduction Glenoid component wear and loosening is the Achilles heel of total shoulder replacement. Analysis of failed, revised implants may give an insight into the causes of component failure.